Settling in or passing through: differentiating between wood‐boring beetle visitation and colonization after a dead wood pulse. Issue 10 (25th October 2018) - Gandiaga, F.; Thibault, M.; Nadeau, P.; Moreau, G.
Abstract: To determine the effect of resource pulses on animal communities, it is important to differentiate the species colonizing the resource substrate from the ones simply moving through the system. In a manipulative field study, we surveyed the response of wood‐boring beetles (Coleoptera) to the small debris produced by commercial thinning operations in white spruce plantations using two methods. First, we sampled the wood‐boring beetles visiting the plantations using flight intercept traps. Then, at the end of the resource pulse in fresh woody debris, we documented the abundance of beetle emergence holes on vertical and horizontal woody debris, which indicate wood‐boring beetle colonization. Results demonstrated that the small horizontal debris generated by commercial thinning were used by saproxylic beetles but were not a preferred resource for colonization, by contrast with vertical dead wood. Only small‐body beetles colonized the horizontal debris and most debris were not colonized. Vertical dead wood, even if present in relatively small quantity when compared to horizontal dead wood, was a major determinant of beetle colonization and community composition. Biomass removal was shown to have a strong detrimental impact on beetle colonization rates. Based on these results, we suggest that most of the saproxylic species trapped after commercial thinning operations were attracted in response to the initial pulse of resource but did not actually colonize the debris from thinning. Thus, we stress the importance of distinguishing between species visitation and colonization following a resource pulse when sampling relies on indirect trapping methods. Abstract : To determine the effect of resource pulses, it is important to differentiate tourists from the species colonizing the resource. Visitation and colonization by wood‐boring beetles (Coleoptera) of areas subjected to commercial thinning were documented. Small woody debris produced by commercial thinning were attractive to beetles but inadequate to fulfill the ecological needs of most species.